The application potential of iMSCs and iMSC-EVs in diseases - Zhou, Xin; Liu, Jinyu; Wu, Feifeng; Mao, Jueyi; Wang, Yang; Zhu, Junquan; Hong, Kimsor; Xie, Haotian; Li, Binbin; Qiu, Xinying; Xiao, Xiangbin; Wen, Chuan (Frontiers in Bioengineering and Biotechnology, 2024)
The immune system, functioning as the body's "defense army", plays a role in surveillance, defense. Any disruptions in immune system can lead to the development of immune-related diseases. Extensive researches have demonstrated the crucial immunoregulatory role of mesenchymal stem cells (MSCs) in these diseases. Of particular interest is the ability to induce somatic cells under specific conditions, generating a new cell type with stem cell characteristics known as induced pluripotent stem cell (iPSC). The differentiation of iPSCs into MSCs, specifically induced pluripotent stem cell-derived mesenchymal stem cells (iMSCs), hold promise as a potential solution to the challenges of MSCs, potentially serving as an alternative to traditional drug therapies. Moreover, the products of iMSCs, termed induced pluripotent stem cell-derived mesenchymal stem cell-derived extracellular vesicles (iMSC-EVs), may exhibit functions similar to iMSCs. With the biological advantages of EVs, they have become the focus of "cell-free therapy". Here, we provided a comprehensive summary of the biological impact of iMSCs on immune cells, explored the applications of iMSCs and iMSC-EVs in diseases, and briefly discussed the fundamental characteristics of EVs. Finally, we overviewed the current advantages and challenges associated with iMSCs and iMSC-EVs. It is our hope that this review related to iMSCs and iMSC-EVs will contribute to the development of new approaches for the treatment of diseases.